Co-occurrence of TCF3-PBX1 gene fusion, and chromosomal aberration in a pediatric pre-B cell acute lymphoblastic leukemia with clitoris swelling: A case report and literature review. Issue 8 (26th February 2021) - He, Guo-qian; Guo, Xia; Jiang, Ming-yan; Xu, Rong-rong; Dai, Yi-ling; Luo, Lili; Gao, Ju
Abstract: Rationale: Clitoris swelling as the initial clinical presentation of acute lymphoblastic leukemia (ALL) is extremely rare. These patients may be misdiagnosed with acute myeloid leukemia or solid tumor, and the main treatment can also be delayed. Patient concerns: A 2.10-year-old girl was referred to the pediatric surgery clinic with a worsening onset of clitoris swellings. The patient was afebrile and well appearing. Multiple retroperitoneal mass were confirmed by computed tomography (CT) and high serum neuron-specific enolase level was high. She was scheduled for an abdominal biopsy from the retroperitoneal mass suspicious of neuroblastoma. Diagnoses: The child was eventually diagnosed as having precursor B cell ALL with central nervous system involved, with TCF3-PBX1 fusion gene and additional chromosomal aberrations, based on examinations of the bone marrow and brain magnetic resonance imaging. Interventions: Before the diagnosis of leukemia, the patient was given symptomatic treatment for 1 week. She was treated with chemotherapy in accordance with the Chinese Children's Cancer Group protocol 2015 after confirmed diagnosis. Outcomes: After induction chemotherapy for ALL, although the girl had transiently clinical remission, the bone marrow aspirate indicated a poor outcome. Our patient discontinued treatment and discharged. From literature review, there was only 1 case of in acute myeloid leukemia with clitoris swelling as the initial symptom. Lessons: The clinical symptoms of ALL with clitoris swelling are not typical, with a high rate of misdiagnosis. When the cause of clitoris swelling is unknown, ALL should be considered. Bone marrow aspiration must be done before doing a more invasive investigation like biopsy.